Beyond the Average: Ethnic Capital Heterogeneity and Intergenerational Transmission of Education - Tanika Chakrabortya; Simone Schüller; Klaus F. Zimmermann (Global Labor Organization (GLO), 2019)
Estimating the effect of ethnic capital on human capital investment decisions is complicated by the endogeneity of immigrants' location choice, unobserved local correlates and the reflection problem. We exploit the institutional setting of a rare immigrant settlement policy in Germany, that generates quasi-random assignment across regions, and identify the causal impact of heterogeneous ethnic capital on educational outcomes of children. Correcting for endogenous location choice and correlated unobservables, we find that children of low-educated parents benefit significantly from the presence of high-educated parental peers of the same ethnicity. High educated parental peers from other ethnicities do not influence children's learning achievements. Our estimates are unlikely to be confounded by the reflection problem since we study the effects of parental peers' human capital which is pre-determined with respect to children's outcomes. Our findings further suggest an increase in parental aspirations as a possible mechanism driving the heterogeneous ethnic capital effects, implying that profiling peers or ethnic role models could be important for migrant integration policies.
Keywords: R23; J15; I21; 330; Education; Ethnic Capital; Germany; Peer Effects; Policy Experiment